Gatekeepers for pragmatic clinical trials. (October 2015) - Whicher, Danielle M; Miller, Jennifer E; Dunham, Kelly M; Joffe, Steven
To successfully implement a pragmatic clinical trial, investigators need access to numerous resources, including financial support, institutional infrastructure (e.g. clinics, facilities, staff), eligible patients, and patient data. Gatekeepers are people or entities who have the ability to allow or deny access to the resources required to support the conduct of clinical research. Based on this definition, gatekeepers relevant to the US clinical research enterprise include research sponsors, regulatory agencies, payers, health system and other organizational leadership, research team leadership, human research protections programs, advocacy and community groups, and clinicians. This article provides a framework to help guide gatekeepers' decision-making related to the use of resources for pragmatic clinical trials. Relevant ethical considerations for gatekeepers include (1) concern for the interests of individuals, groups, and communities affected by the gatekeepers' decisions, including protection from harm and maximization of benefits; (2) advancement of organizational mission and values; and (3) stewardship of financial, human, and other organizational resources. Separate from these ethical considerations, gatekeepers' actions will be guided by relevant federal, state, and local regulations. This framework also suggests that to further enhance the legitimacy of their decision-making, gatekeepers should adopt transparent processes that engage relevant stakeholders when feasible and appropriate. We apply this framework to the set of gatekeepers responsible for making decisions about resources necessary for pragmatic clinical trials in the United States, describing the relevance of the criteria in different situations and pointing out where conflicts among the criteria and relevant regulations may affect decision-making. Recognition of the complex set of considerations that should inform decision-making will guide gatekeepers in making justifiable choices regarding the use of limited and valuable resources.